Severity of Intrarenal Arterial Lesions Can Predict the Clinical Prognosis of Hepatitis B Virus-Associated Glomerulonephritis: A Retrospective Study - Yongze Zhuang; Bo Liu; Yinghao Yu; Tianjun Guan; Zhiyong Zheng; Anqun Chen (Karger Publishers, 2020)
Background: Intrarenal arterial lesions (IALs) have been studied in immunoglobulin A nephropathy and lupus nephritis, but this has not been reported in hepatitis B virus-associated glomerulonephritis (HBV-GN). This study aims to investigate the prevalence and the role of IALs in HBV-GN. Methods: IALs were examined in kidney biopsy specimens from 205 patients with HBV-GN retrospectively. The severity of IALs and tubular interstitial lesions was scored semi-quantitatively. The severity of IALs was divided into 4 groups on the basis of ILA score, which were no IALs (Score 0), mild IALs (Score 1-2), moderate IALs (Score 3-4), and severe IALs (Score 5-10) groups. Survival analysis was performed using the Kaplan-Meier method between the severity of IALs and clinical events (doubling of serum creatinine [SCr], ESRD, and death due to the kidney disease). Results: Among 205 patients with HBV-GN, 143 (69.8%) had IALs in their kidney biopsy specimens. IALs were mild in 28 (19.6%) patients, moderate in 101 (70.6%) patients, and severe in 14 (9.8%) patients. The severity of IALs was associated with high blood pressure (BP), high SCr, and severe tubulointerstitial injuries. The average follow-up time of these 205 HBV-GN patients was 94.2 ± 47.1 months, in which 46 cases had clinical event. The proportions of clinical events in no IAL, mild IAL, moderate IAL, and severe IAL groups were 9.7, 14.3, 25.7, and 71.4%, respectively. Event-free survival of patient in IAL group was significantly lower than that in the no IAL group (p = 0.000). Multivariate cox regression analysis indicated SCr (1.011, 1.007-1.016), hypertension (1.767, 1.004-3.108), and IAL (2.194, 1.062-4.530) were independent risk factors for clinical events after adjustment for age and gender. Event-free clinical survival in moderate and severe IAL groups was significantly lower than that in the no IAL group (p = 0.0111 and p = 0.0001, respectively). Besides, event-free renal survival in severe IAL group was significantly lower than that in moderate IAL group (p = 0.009). Multivariate cox regression analysis showed that the more severe the IALs, the higher the risk of the clinical event, with a hazard ratio of 2.284 for moderate IALs (1.085-4.907) and 3.315 for severe IALs (1.296-8.482). Conclusions: Severity of IALs is associated with high BP, reduced renal function, and poor clinical prognosis in HBV-GN patients.